Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual Dan Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Billman Pada PT. PLN (Persero) Indarung Padang - Aminar Sutra Dewi; Putri Lestari Ramadhani (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate     Fast traslate Icon translate The success of a company in achieving its goals is highly dependent on human resources working in an organization, but to be able to achieve goals must be based on the principles of efficiency and effectiveness. The role of human resources is very important in an organization, both for profit and non-profit organizations. The success of an organization is very important. influenced by the performance of an employee. This study aims to test emotional intelligence on employee performance, to test intellectual intelligence on employee performance, to test job satisfaction on employee performance. The sampling method uses a saturated total sampling of 30 samples, using normality testing and multiple linear regression. The results showed that emotional intelligence has a positive and significant effect on employee performance. Intellectual intelligence has a negative and insignificant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance.